Design Of Automatic Hand Sanitizer Spray System Based On Arduino Uno Using Fuzzy Logic Method - Firhan Ali; Husnul Khair; Imeldawaty Gultom (International Journal of Health Engineering and Technology, 2024)
Washing hands is the act of cleaning like fingers to wrists using water or other liquids. Hand sanitizer with a minimum alcohol content of 60% is believed to be effective for killing germs and other harmful microorganisms because hands are one part of the body that often interacts such as touching and can be a medium for the spread of viruses, germs and bacteria. The manufacture of tools is carried out as one of the efforts in advancing technology to provide convenience and comfort through the development of an automatic system for hand sanitizer containers. From the above problems an Arduino based automatic hand sanitizer system was created. This system works directly to be able to spray liquid automatically. This system is expected to make it easier for users to spray liquids without having to do it manually or touching the container directly to maximize time efficiency and keep it clean. By designing a prototype to make this automatic hand sanitizer using an ultrasonic sensor as input, Arduino Uno Atmega328p as a microcontroller, and a servo motor as a driver for the hand sanitizer container. The system on the tool to be made is capable of spraying liquid automatically at a maximum distance of 10 centimeters.